Skuteczność działań promocyjnych biur podróży - Przeorek-Smyka, Renata (The Effectiveness of Travel Offices' Promotional Activities, 2005)
The article presents ways for measuring the effectiveness of promotion and the level of realization of sales boosting targets in travel offices. The results of research conducted by the author in the area of Lower Silesia and Opolskie Silesia regions have become the basis for the presented concept analysis. Besides, the article defines the notion of effectiveness, characterizes stages of the process of marketing communication effectiveness evaluation, as well as emphasizes problems encountered in performing practical measurement of the discussed phenomenon.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 211-225